PHYSICOCHEMICAL SENSORS FOR THE DETERMINATION OF SILVER - Mahmoud, Wagiha , H.; EL-hag, Fatma Abdul Aleem; AL –Harbi, Reem A.K. (European Scientific Journal, ESJ, 2013)
A novel silver sensor based on 3,7- dimethoxy -6-hydroxy benzofuran-5- carboxylic acid as an ionophore for ion-selective polymeric membrane electrode toward Ag+1 ions was examined. The sensor showed a near Nernstian response for Ag +1 ions over a concentration range 1x10-6 to 1.0×10-2 mol L-1 with a slope of 61± 0.4 mV per concentration decade in an acidic solution (pH 5). The limit of detection was 0.47 mg mL-1. It had a response time of < 20 s and can be used for at least 3 months without any divergence in potentials. The influence of plasticizer as well as the amount of lipophilic anionic site additive in the sensing membrane was discussed. It was shown that membrane electrodes formulated with the ionophore and appropriate anionic additive exhibited enhanced potentiometric response toward Ag+1 over all other cations tested. Validation of the assay method revealed good performance characteristics, including long life span, good selectivity for Ag1+ ions over a wide variety of other metal ions, long term response stability, and high reproducibility. The sensors were used for direct measurement of silver content in different rocks collected from different geological zones. The results agreed fairly well with data obtained using atomic absorption spectrometry.